UPAYA PENINGKATAN KESADARAN MASYARAKAT DALAM PENGEMBANGAN DIVERSIFIKASI PRODUK OLAHAN PANGAN BERBASIS PANGAN LOKAL MELALUI KEGIATAN IbM DI DESA GILANGHARJO, KABUPATEN BANTUL - Suryani, Chatarina Lilis; Yulianto, Wisnu Adi; Aiman, Umul (Universitas Negeri Yogyakarta, 2015)
Gilangharjo village is a village with diverse tourism potential which lies between the golden triangle area of Bantul. Besides, Gilangharjo village alsohas a high potential in agriculture, even the dry land such as large gardens andyards with the main results of bananas and fisheries. However, these lands havenot been fully utilized yet. In accordance with the mission of Village Gilangharjo, which is to strengthen the productive group institutionally business in small food industry now has been developed. Based on the analysis results of the situation, it is identified that problems faced by food Small Medium and Enterprises (SMEs) in the village Gilangharjo, specifically in Jodog and Karanganom village-district, are the absence of the processing technology implementation for diversified food processed product based on local food, improper food production and packaging process, as well as not-well-organized business and finance management. The purpose of the activity proposed is to raise awareness of the public, especially members of the SME I and SME II, in improving food diversification based on local food. Method of implementation is divided into stages of (i) coordination and tools preparation, (2) science and technology application which is consisted of socialization, education and training, as well as monitoring and evaluation steps. Counseling given to the society are about packaging and labeling, food safety and good production process, manufacturing process of catfish and bananas, production and finance management, and ended by evaluation using a questionnaire instrument. Questionnaire results showed that counseling and training activities are able to enhance the knowledge and skills of local food processing, specifically catfish and banana. By this activity, the members of both SME I and SME II are motivated to increase production of processed food based on local food, specifically catfish and banana,either in groups or individually